Quantized chiral anomaly materials cloak - Lunwu Zeng (Nature Portfolio, 2017)
Abstract Chiral anomaly materials (CAM, e.g., axion insulator, topological insulator and some of Weyl semimetal) are new states of quantum matter. Anomalous Hall effect can occur in CAM, the anomalous Hall effect is closely related to the topological magneto-electric effect, i.e., when an electric field is applied to CAM, not only the electric field is induced, but also the magnetic field, vice versa. According to those properties, we design an electric cloak with quantized CAM and conductor, and a magnetic cloak with quantized CAM and superconductor. Simulation and calculation results show that the electric cloak can cloak applied electric field and induce magnetic field, and the magnetic cloak can cloak applied magnetic field and induce electric field. When applied electric field is generated by a point charge, the monopole can be obtained.